High prevalence of hypertension and target organ damage in patients with 11β‐hydroxylase deficiency. (3rd February 2022) - Sun, Bang; Lu, Lin; Gao, Yinjie; Yu, Bingqing; Chen, Shi; Tong, Anli; Wu, Xueyan; Mao, Jiangfeng; Wang, Xi; Zhao, Zhiyuan; Zhang, Wei; Nie, Min
Abstract: Background: Prevalence of hypertension and hypertension‐mediated organ damage (HMOD) had not been well studied in patients with 11β‐hydroxylase deficiency (11β‐OHD). Objective: The study was to assess the prevalence and risk factors of hypertension and HMOD in patients with 11β‐OHD. Design: Retrospective cohort analysis in a single medical centre. Patients: Twenty‐eight patients with 11β‐OHD were recruited between January 2003 and June 2021, and their diagnosis had been confirmed by Sanger sequencing. Measurements: Blood pressure and clinical indicators for the assessment of HMOD occurrence were collected from the medical records. Medication adherence of antihypertensive drugs and glucocorticoids were determined by the patients' biochemistry. Logistic regression was used to identify factors associated with HMOD. Results: Prevalence of hypertension and HMOD in the cohort was 100% and 50%, respectively. The kidneys (71.43%) are the organ most commonly damaged by high blood pressure, followed by the heart (64.29%), eyes (57.14%) and brain (21.43%). Risk factors of HMOD were hypokalemia (odds ratio [OR]: 9.16; 95% confidence interval [CI]: 1.634–51.43; p  = .012), blood pressure ≥ 180/110 mmHg (OR: 22.0, 95% CI: 3.08–157.34; p  = .002) and irregular glucocorticoid use (OR: 3.18, 95% CI: 1.13–8.98; p  = .021). Blood pressure ≥ 180/110 mmHg was an independent predictor for HMOD. Conclusion: Hypertension and HMOD are prevalent in patients with 11β‐OHD in our study. These findings illustrate the importance of early HMOD evaluation and optimal glucocorticoid medication in 11β‐OHD patients.